Mindfulness as a Moderator of the Association Between Eating Disorder Cognition and Eating Disorder Behavior Among a Non-clinical Sample of Female College Students: A Role of Ethnicity - Masuda, Akihiko; Marshall, Rachel D.; Latner, Janet D. (Frontiers in Psychology, 2018)
The present cross-sectional study examined whether mindfulness moderated the association between eating disorder cognition and eating disorder behaviors among Asian American, Black American, and White American female college students in the U.S. Participants (N = 463, age range = 18-25 years) completed self-report measures online. Results revealed that mindfulness moderated the association between eating disorder cognition and eating disorder behavior in the White American group, but not in Asian American or Black American samples. Future research should replicate these differential findings across ethnic groups and investigate the factors that may contribute to this group difference.